Closantel plasma and milk disposition in dairy goats: assessment of drug residues in cheese and ricotta - Iezzi, Sebastián Juan (2014)
Closantel (CLS) is currently used in programs for the strategic control of gastrointestinal nematodes. CLS is extralabel used in different dairy goat production systems. From available data in dairy cows, it can be concluded that residues of CLS persist in milk. The current work evaluated the concentration profiles of CLS in plasma and milk from lactating orally treated dairy goats to assess the residues pattern in dairy products such as cheese and ricotta. Six (6) female Saanen dairy goats were treated orally with CLS administered at 10 mg/kg. Blood and milk samples were collected between 0 and 36 days post-treatment. The whole milk production was collected at 1, 4, 7, and 10 days post-treatment to produce soft cheese and ricotta. CLS concentrations in plasma, milk, cheese, whey, and ricotta were determined by HPLC. The concentrations of CLS measured in plasma were higher than those measured in milk at all sampling times. However, the calculated withdrawal time for CLS in milk was between 39 and 43 days postadministration to dairy goats. CLS residual concentrations in cheese (between 0.93 and 1.8 μg/g) were higher than those measured in the milk used for its production. CLS concentrations in ricotta were sixfold higher than those in the milk and 20-fold higher than those in the whey used for its production. The persistent and high residual concentrations of CLS in the milk and in the cheese and ricotta should be seriously considered before issuing any recommendation on the extralabel use of CLS in dairy goat farms.